2008
DOI: 10.1111/j.1538-7836.2008.02894.x
|View full text |Cite
|
Sign up to set email alerts
|

A unique function for LRP‐1: a component of a two‐receptor system mediating specific endocytosis of plasma‐derived factor V by megakaryocytes

Abstract: Summary. Background: Factor V is endocytosed by megakaryocytes from plasma via a specific, receptor-mediated, clathrin-dependent mechanism to form the unique plateletderived FV pool. Objective: The role of low-density lipoprotein (LDL) receptor-related protein-1 (LRP-1), or a related family member, in FV endocytosis by megakaryocytes was examined because of its known interactions with other proteins involved in hemostasis. Methods: LRP-1 expression by megakaryocytes and its functional role in FV endocytosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…Alternatively, binding of PF4 to LRP1 may prevent interaction with another ligand that would then promote proliferation. Our shRNA and anti-LRP1 blocking antibody in vitro megakaryocyte colonyformation studies data suggest that the former mechanism is more likely given that directly blocking LRP1 results in an increase in megakaryocyte colony formation.While our studies were under way, Bouchard et al reported the presence of LRP1 on human megakaryocytes and its role in the endocytosis of factor V. 18 Our studies confirm their observation that LRP1 is present on the surface of megakaryocytes. In addition, we extended these findings to show that this receptor is only transiently expressed during megakaryopoiesis.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Alternatively, binding of PF4 to LRP1 may prevent interaction with another ligand that would then promote proliferation. Our shRNA and anti-LRP1 blocking antibody in vitro megakaryocyte colonyformation studies data suggest that the former mechanism is more likely given that directly blocking LRP1 results in an increase in megakaryocyte colony formation.While our studies were under way, Bouchard et al reported the presence of LRP1 on human megakaryocytes and its role in the endocytosis of factor V. 18 Our studies confirm their observation that LRP1 is present on the surface of megakaryocytes. In addition, we extended these findings to show that this receptor is only transiently expressed during megakaryopoiesis.…”
supporting
confidence: 87%
“…18 Briefly, 4 ϫ 10 5 purified human CD34 ϩ cells were cultured in media consisting of IMDM with 10 mg/mL BSA (Sigma-Aldrich), 740 g/mL partially saturated transferrin (Sigma-Aldrich), 10 g/mL human insulin (Sigma-Aldrich), 40 g/mL low-density lipoprotein (Calbiochem), 2 mM L-glutamine (Fisher), and 100 ng/mL recombinant human TPO (R&D Systems). Cells were incubated at 37°C and medium was replaced on days 4, 7, 11, and 14 of culture.…”
Section: Bone Marrow Cell Cultures Rt-pcr Flow Cytometry and Westementioning
confidence: 99%
“…5,6 Although megakaryocytes are capable of FV synthesis, 7,8 platelet FV originates from the plasma pool. [9][10][11] Bone marrow megakaryocytes internalize plasma FV via a specific receptormediated process 12 and store it in secretory ␣-granules. 13 After endocytosis, FV gains several unique modifications that make platelet FV structurally and functionally different from plasma FV.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that Gal8 may also require a counter receptor to mediate the uptake of FV. Interestingly, Bouchard et al (22) previously proposed that FV uptake by megakaryocytes involves a two-step mechanism in which FV first binds an unidentified cell surface element, after which it is transferred to LRP-1 for receptor-mediated endocytosis. If so, our data suggest that the initial binding event may involve Gal8.…”
Section: Discussionmentioning
confidence: 99%
“…The actual mechanism behind the endocytic uptake of FV, however, is still unclear. It has been proposed that FV first binds to the cell surface via an unknown cellular component, after which it is internalized via low density lipoprotein receptor-related protein 1 (LRP-1) (22).…”
mentioning
confidence: 99%